Deployment of a stand‐alone hybrid renewable energy system in coastal areas as a reliable energy source. Issue 3 (21st October 2019) - Kasaeian, Alibakhsh; Razmjoo, Armin; Shirmohammadi, Reza; Pourfayaz, Fathollah; Sumper, Andreas
Abstract: Solar and wind can be considered as sustainable environmentally friendly and omnipresent renewable energy sources for generating a part of required electrical energy for inhabitants of the remote areas in different countries. Accordingly, this study investigates the techno‐economic evaluation for two‐hybrid renewable energy systems for Bandar Dayyer. The findings of this study shows that using the HOMER software, the total amount of electricity production by these systems are equal to 470, 176 kW, of which 22, 409 kW is provided by PV‐generic system and 447, 767 kW is supplied by PV‐diesel‐generic system. It should be mentioned that this area has an appropriate potential of wind speed and solar radiation; therefore, the area can be suitable for investing on a hybrid renewable energy site.